Gontor as Waqf-based Pesantren : A Review - Mimma Maripatul Uula (The Economic Review of Pesantren, 2023)
This research aims to see the development of research on the topic "Gontor Waqf” and research plans that can be carried out based on journals published on that theme. This research uses qualitative methods with a bibliometric analysis approach. The data used is secondary data with the theme "Gontor Waqf” which comes from the Dimension database with a total of 43 journal articles. Then, the data is processed and analyzed using the VosViewer application with the aim of knowing the blibliometric map of research development "Gontor Waqf" in this world. The results of the research found that in bibliometric author mapping the authors published the most research with the theme "Gontor Waqf” is Shulthoni, Muhammad; Syamsuri, Syamsuri; Mahendra, Mahendra; Rofiqo, Azidni; bin Lahuri, Setiawan; Muqorobin, Ahmad and Bahroni. Furthermore, based on bibliometric keyword mapping, there are 4 clusters that can be research lines with topics related to (1) Corporate Social Responsibility (CSR) and Gontor Waqf, (2) Management of Islamic boarding school waqf and Gontor Waqf, (3) Education and Gontor Waqf, and (4) Responsibilities of Waqf Institutions and Gontor Waqf. Furthermore, the words most used are pesantren, productive waqf, Islamic boarding school, Darussalam Gontor, student, and community.